2015
DOI: 10.1111/jam.12877
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of pathogenic bacteria inoculated onto a Bactoagar model surface using TiO2-UVC photocatalysis, UVC and chlorine treatments

Abstract: The results showing effects of photocatalysis and other treatments for inactivation of bacterial pathogens on model surface can be useful for applying such processes for disinfection of fruit, vegetables and other similar surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These reductions were found to be much higher than the reductions achieved by NaOCl, and UV treatments alone. Similarly, Yoo and others () reported a 4.5 to 6 log CFU/cm 2 reduction of E.coli K12, S. typhimurium , S. aureus , and L. monocytogenes from an artificial food surface model using a TiO 2 –UVC photoreactor. This treatment was shown to have potential to disinfect fruit, vegetable, and other similar food product surfaces.…”
Section: Semiconductor Metal Oxide Surface Coatingsmentioning
confidence: 74%
“…These reductions were found to be much higher than the reductions achieved by NaOCl, and UV treatments alone. Similarly, Yoo and others () reported a 4.5 to 6 log CFU/cm 2 reduction of E.coli K12, S. typhimurium , S. aureus , and L. monocytogenes from an artificial food surface model using a TiO 2 –UVC photoreactor. This treatment was shown to have potential to disinfect fruit, vegetable, and other similar food product surfaces.…”
Section: Semiconductor Metal Oxide Surface Coatingsmentioning
confidence: 74%
“…This precedence order is confirmed in the literature, being attributed to Gram-positive species possessing a thick cell wall with many layers of peptidoglycan and teichoic acids, which potentially preserves the bacterial viability during disinfection. 36 Nevertheless, this is not always the case, as the outer membrane of Gram-negative bacteria counteracts the lack of a thick wall, resulting in requirement of high catalyst concentrations up to 300 mg L −1 for complete elimination. 37…”
Section: Bacterial Inactivationmentioning
confidence: 99%
“…Recently, researchers evaluated the effect of TUV treatment on pathogenic microorganisms including E. coli K12, S. Typhimurium, S. aureus, and L. monocytogenes inoculated on the surface of Bacto TM agar model (Yoo et al, 2015b). TUV treatment reduced the microbial load by 4.5-6.0 log CFU/cm 2 whereas UV alone treatment led to a 3.0-5.3 log CFU/cm 2 reduction.…”
Section: Surface Disinfection Of Model Foodsmentioning
confidence: 99%
“…Altering the technique by addition of TiO 2 may greatly influence consumer acceptance (Cho et al, 2007;Kim et al, 2009;Yoo et al, 2015a). In most research work on food products, TiO 2 is immobilized by coating the quartz tube or the sample holder (Cho et al, 2007;Kim et al, 2009;Chai et al, 2014;Yoo et al, 2015b). Although TiO 2 is immobilized, it has to be confirmed that there are minimal residues in the treated food products (Cho et al, 2007;Kim et al, 2009;Yoo et al, 2015a).…”
Section: F) Need For Consumer Awareness and Acceptancementioning
confidence: 99%
See 1 more Smart Citation